Between suffering and coping: burnout in female medical doctors in South Africa - Oosthuizen, Rudolf M.; Mashego, Keitumetse; Mayer, Claude-Hélène (Frontiers in Psychology, 2023)
Burnout is described as emotional and physical exhaustion, reduced accomplishment, together with an outlook of inadequacy and cynicism related to job stress. It has a harmful impact globally, especially in developing countries, such as South Africa. This study is a phenomenological collective case study focusing on burnout experience in a sample of female medical doctors working in a South African public hospital. Based on ongoing explorations of burnout themes, empirically based intervention strategies are needed to be developed and presented for the South African public health sector to prevent stress-related burnout. The findings support the trend in literature that burnout is an overwhelming experience for female medical doctors in South Africa. The study presents voices of female medical doctors, their concerns, the causes for burnout and their coping mechanisms. It provides a strong contribution to exploring and presenting women’s experiences in working in the medical field in South Africa from a positive psychology perspective. The findings indicate the struggles and the coping mechanisms of female medical doctors working in the field.